The chemical composition of essential oil of Anisomeles indica (L.) Kuntze from Dak Lak province, Vietnam - Thai, Tran Huy; Hien, Nguyen Thi; Thang, Tran Dinh (Academia Journal of Biology, 2014)
Anisomeles indica (L.) Kuntze is a perennial herb, 0.70-1.20 m high. Stem is cylindrical, erect, densely hairy at the top and sides of the stem. Leaves are opposite, oval or ovate, 7-15 ´ 3-6 cm, densely pubescent on both sides. Inflorescence is in terminal spike of underneath loosely arranged whorls. Flowers are impedicellate, pink or purple. Fruits are 4-drupelets, oblong ovate. Fruiting period is from September to March. The yield of essential oil from leaves and fruits of Anisomeles indica (L.) Kuntze was 0.1 percent from air-dry material. By using GC and GC/MS analysis, 37 have been identified which accounts for more than 96.4% of the essential oil. The main constituents of essential oil were a-pinene (32.6%), limonene (26.6%), caryophyllene oxide (10.2%), b- caryophyllene (6.0%) and bornyl acetat (5.2%).